Analysis of Work Posture at PT Kanugrahan Techno Engineering : Application of the REBA Method to Reduce MSDs Risk - Ahmad Zada Hilmi Syifa; Nalan Adha Ilan Ilahi; A Dandi Setiawan; Egga Jerri Indri Saputri; Lulu Rahiba; Widya Setiafindari (International Journal of Mechanical, Industrial and Control Systems Engineering, 2025)
This study aims to analyze the musculoskeletal disorders (MSDs) risk of workers at PT Kanugrahan Techno Engineering involved in grinding activities using the REBA (Rapid Entire Body Assessment) method. The analysis results indicate that grinding activities 1 and 2 have a REBA score of 9, indicating a very high risk, while grinding activity 3 has the highest score of 10, indicating an extreme risk. Grinding activities 4 and 5 have a score of 7, indicating a moderate risk. To reduce these risks, ergonomic aids in the form of a table and chair were designed to support better posture. The production cost of one set of tools is Rp 710,966, with a total cost for 5 sets amounting to Rp 3,554,833.91. The implementation of ergonomic aids is expected to reduce MSDs risks, increase comfort and work efficiency, and improve worker productivity.